“BASHEROV DYNASTY” - Dauletbaeva Gulxumar; Kamalova Gulmaryam (PEDAGOGS, 2023)
Annotation: In this article, we will talk about the history of people like Amanbay hero, Mambetniyaz, who came from the Jagaltay lineage of Khipchak, and their descendants.